2019
DOI: 10.1007/s11095-019-2654-z
|View full text |Cite
|
Sign up to set email alerts
|

Recent Treatment Advances and the Role of Nanotechnology, Combination Products, and Immunotherapy in Changing the Therapeutic Landscape of Acute Myeloid Leukemia

Abstract: Acute myeloid leukemia (AML) is the most common acute leukemia that is becoming more prevalent particularly in the older (65 years of age or older) population. For decades, “7 + 3” remission induction therapy with cytarabine and an anthracycline, followed by consolidation therapy, has been the standard of care treatment for AML. This stagnancy in AML treatment has resulted in less than ideal treatment outcomes for AML patients, especially for elderly patients and those with unfavourable profiles. Over the past… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 182 publications
0
30
0
Order By: Relevance
“…The current treatment paradigm employs remission-inducing chemotherapy, with cytarabine and anthracycline with or without a purine analogue, such as 7 days of standard-dose cytarabine plus 3 days of anthracycline (ie, “7 + 3”), fludarabine–Ara-C–granulocyte colony-stimulating factor–idarubicin, or similar induction, followed by consolidation chemotherapy and/or allogeneic stem cell transplantation (SCT) for patients with a high risk of relapse 5 . This approach has been the mainstay of therapy for the past four decades, achieving complete remission (CR) in 60–80% of patients <60 years of age.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current treatment paradigm employs remission-inducing chemotherapy, with cytarabine and anthracycline with or without a purine analogue, such as 7 days of standard-dose cytarabine plus 3 days of anthracycline (ie, “7 + 3”), fludarabine–Ara-C–granulocyte colony-stimulating factor–idarubicin, or similar induction, followed by consolidation chemotherapy and/or allogeneic stem cell transplantation (SCT) for patients with a high risk of relapse 5 . This approach has been the mainstay of therapy for the past four decades, achieving complete remission (CR) in 60–80% of patients <60 years of age.…”
Section: Introductionmentioning
confidence: 99%
“…This approach has been the mainstay of therapy for the past four decades, achieving complete remission (CR) in 60–80% of patients <60 years of age. Although effective, this approach may be poorly tolerated, with a higher risk of induction mortality in patients with comorbidities, poor performance status, and/or advanced age 5 7 . In addition, unsatisfactory response rates and survival have been reported for conventional chemotherapy in patients with adverse cytogenetic risk or high-risk molecular mutations, such as TP53 (refs.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, increasing studies have demonstrated that inhibition of ER stress had great benefits on the ischemic injured cardiomyocytes (K. T. J. Chen, Gilabert-Oriol, Bally, & Leung, 2019;Shi et al, 2016). Therefore, targeting ER stress might be a promising strategy for treating cardiovascular disorder including hypertension (Walraven et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In particular Vyxeos® has proven very successful in the treatment of adult acute myeloid leukemia. 65 Vyxeos® is a liposomal formulation of daunorubicin and cytarabine. In the phase 3 trials, Vyxeos® demonstrated superior overall survival and reduced risk of death in patients compared to those who were administered the two drugs in a combination regime with no nanotechnology.…”
Section: Nanomedicines Already Approved For Clinical Usementioning
confidence: 99%